Bronchoscopy guided by high-resolution computed tomography for the diagnosis of pulmonary infections in patients with hematologic malignancies and normal plain chest X-ray - E Ramila; A Sureda; R Martino; A Santamaria; T Franquet; C Puzo; J Montesinos; G Perea; J Sierra (Haematologica, 2000)
BACKGROUND AND OBJECTIVES: High-resolution computed tomography (HRCT) of the chest is able to demonstrate the presence of pulmonary infiltrates in febrile neutropenic patients with normal chest X-rays. Fiberoptic bronchoscopy with bronchoalveolar lavage (BAL) is a safe procedure for the etiological diagnosis of pulmonary infiltrates in oncohematologic patients. The objective of this study was to determine the diagnostic yield and subsequent therapeutic changes of a protected BAL (p-BAL) guided by HRCT in febrile oncohematologic patients unresponsive to broad-spectrum antibiotics with a normal chest X-ray. DESIGN AND METHODS: Twenty-two episodes from 20 oncohematologic patients were included: group A, 9 episodes (8 patients) with no respiratory symptoms and group B, 13 episodes (12 patients) with signs or symptoms of pulmonary infection. HRCT and p-BAL were performed in all episodes within the first 24 hours. RESULTS: HRCT showed abnormalities in all 22 episodes (bilateral abnormalities in 14 of the 22 episodes [64%]) and the most frequent pattern was ground-glass infiltrate (7 out of 22 episodes). An infectious agent was isolated in 12 of the 22 episodes, 5 in group A and 7 in group B with a diagnostic yield of 54%. Antimicrobial therapy was modified in 12 of the 22 episodes (54%): 5 in group A and 7 in group B. In 6 episodes, treatment was changed according to HRCT results and in the remaining 6 due to positive microbiologic results. Modifications in empirical therapy were associated with a favorable response in 44% episodes of group A and in 31% of group B. INTERPRETATION AND CONCLUSIONS: Oncohematologic patients with fever of unknown origin unresponsive to empirical antibiotics and with a normal chest X-ray can be candidates to undergo a HRCT. This subgroup of high-risk patients can benefit from a combined strategy consisting of BAL guided by a previous HRCT.